已知函数f(x)=x-4
(Ⅰ)求证:数列{
(Ⅱ)若cn=
|
(Ⅰ)证明:∵函数f(x)=x-4
+4(x≥4),即y=x-4x
+4(x≥4),x
∴x=
+2(y≥0),∴f-1(x)=(y
+2)2 (x≥2),x
∴an+1=f-1(an)=(
+2)2,an
即
-an+1
=2 (n∈N*).an
∴数列{
}是以an
=1为首项,公差为2的等差数列.a1
(Ⅱ)由(Ⅰ)得:
=1+2(n-1)=2n-1,an
即an=(2n-1)2 (n∈N*).
由b1=1,当n≥2时,bn-bn-1=1×(
)n-1=(1 3
)n-1,1 3
∴bn=b1+(b2-b1)+(b3-b2)+…+(bn-bn-1)
=1+
+(1 3
)2+…+(1 3
)n-11 3
=1×(1-(
)n)1 3 1- 1 3
=
(1-3 2
).1 3n
因而bn=
(1-3 2
) (n∈N*).1 3n
由cn=
•bn,得:cn=an
•(2n-1)2
(1-3 2
)=1 3n
(2n-1)(1-3 2
),1 3n
∴Sn=c1+c2+…+cn
=
(1-3 2
)+1 3
(3-3 2
)+3 32
(5-3 2
)+…+5 33
(2n-1-3 2
)2n-1 3n
=
[(1+3+5+…+2n-1)-(3 2
+1 3
+3 32
+…+5 33
)].2n-1 3n
令Tn=
+1 3
+3 32
+…+5 33
①2n-1 3n
则
Tn=1 3
+1 32
+3 33
+…+5 34
+2n-3 3n
②2n-1 3n+1
①-②得,
Tn=2 3
+2(1 3
+1 32
+…+1 33
)-1 3n 2n-1 3n+1
=
+1 3
-2×
(1-1 9
)1 3n-1 1- 1 3 2n-1 3n+1
=
+1 3
(1-1 3
)-1 3n-1
.2n-1 3n+1
∴Tn=1-
.n+1 3n
又1+3+5+…+(2n-1)=n2.
∴Sn=
(n2-1+3 2
).n+1 3n